Bleeding and quality of life in people with Glanzmann thrombasthenia—insights from the Glanzmann’s 360 study - Khair, Kate; Fletcher, Simon; Boyton, Matthew; Holland, Michael (Research and practice in thrombosis and haemostasis, 2024)
Glanzmann thrombasthenia (GT) is a rare platelet function disorder that results in severe bleeding. We assessed clinical symptoms and psychological parameters to identify the unmet needs associated with GT. Glanzmann’s 360 is a mixed-methods study designed to give a contemporary snapshot of the impact of living with GT. The study comprised a self-completion online survey complemented by interviews conducted with affected individuals and carers recruited via social media and hemophilia treatment centers. The survey was completed by 88 people with GT and 29 carers of children/young people with GT aged <16 years. The population ranged in age from <2 years to >70 years; 56% were female. Although 47% had been diagnosed with GT under the age of 2 years, 12% were diagnosed after 20 years of age. For 82%, a bleeding phenotype was apparent by the age of 5 years. Most respondents (88%) had experienced at least one bleed in the past week. Bleeding disproportionally affected women. Bleeds resulted in frequent hospital contact and considerable psychological distress: 26% of the population had scores suggestive of low self-esteem, while 30% met criteria suggestive of symptomatic depression. Exploratory analyses suggest that bleed experiences are associated with impaired health-related quality of life. The Glanzmann’s 360 study reveals the significant physical, psychosocial, and quality-of-life impairments that are likely to be linked to the frequent bleeds experienced by those with GT. Clinicians treating people with GT should promote access to multidisciplinary comprehensive care, including psychosocial support. •Glanzmann thrombasthenia is a rare platelet function disorder resulting in severe bleeding.•This mixed-methods study (88 adults and 29 carers) gives a contemporary snapshot of life with Glanzmann thrombasthenia.•Most had bled in the last week, causing distress; women were more affected than men.•Significant physical, psychosocial, and quality-of-life impacts are linked to frequent bleeding.